2019
DOI: 10.3390/cancers11040488
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Thromboembolism after Lobectomy for Lung Cancer: Pathological Diagnosis and Mechanism of Thrombus Formation

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. Although molecular therapies have emerged as efficacious strategies for the treatment of lung cancer, surgical resection is still recommended as a radical therapeutic option. Currently, lobectomy is regarded as the most reliable radical treatment of primary lung cancer. Among the various complications after lobectomy, cerebral thromboembolism requires attention as a life-threatening complication during the early postoperative period. It occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…Previous researches indicated that endothelial injury and immune cells plays an important role in thrombogenesis in the PVS. 4,12 In our case, after dividing the draining veins with stapler, interlocking nails stabed into the endothelium and leaved behind in the tissue of PVS. Endothelial injury consequently activated the extrinsic pathway of the coagulation cascade and resulted in thrombus formation in the PVS.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Previous researches indicated that endothelial injury and immune cells plays an important role in thrombogenesis in the PVS. 4,12 In our case, after dividing the draining veins with stapler, interlocking nails stabed into the endothelium and leaved behind in the tissue of PVS. Endothelial injury consequently activated the extrinsic pathway of the coagulation cascade and resulted in thrombus formation in the PVS.…”
Section: Discussionmentioning
confidence: 63%
“…10,11 Cerebral embolism is a serious complication in the early postoperative period, occurring in 0.2-1.2% of surgical lung cancer cases. 12 In this case, we present an rare case of cerebral embolism after segmentectomy. There was only one risk factor for cerebrovascular disease (long-term smoking history) before surgery, and relevant preoperative examination did not indicate the risk of cerebral embolism ( AF and Hypercoagulability).…”
Section: Discussionmentioning
confidence: 93%
“…Its etiology of PVT has not been completely solved; several mechanisms of thrombus formation, such as the PV stump after VATS-LUL was longer than the other PV stumps and lower bloodstream velocity and more turbulent flow in the dissected PV stump than that in other PV stumps, were suggested [3,9,11]. Endothelial injury or surgical staples also can play an important role in thrombogenesis in the PV stump after lung resection [12]. A recent study showed that central vascular ligation of PV stump may reduce intravascular exposure of the staple and contribute to a short PV stump and then contribute to reduce incidence of PVT [10].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal antithrombotic therapy and preventive approaches for PVT remains unestablished, it should be noted that early recognition of PVT and anticoagulant therapy is important to prevent massive cerebral embolism [12]. The induction time and the duration of anticoagulation therapy are difficult to determine because PVT can occur even after the next day of discontinuation of anticoagulant therapy [13,14] and can be a possible cause of cerebral embolism anytime after lung resection.…”
Section: Discussionmentioning
confidence: 99%
“…it also be associated with fewer postoperative complications and better lung function [ 10 , 11 ]. Cerebral embolism is a serious complication in the early postoperative period, occurring in 0.2–1.2% of surgical lung cancer cases [ 12 ]. In this case, we present an rare case of cerebral embolism after segmentectomy.…”
Section: Discussionmentioning
confidence: 99%